Особливості біосинтезу позаклітинних целюлаз і ксиланази у Fennellia flavipes B.J. Wiley et E.G. Simmons - Сирчин, С.О.; Харкевич, О.С.; Павличенко, А.К.; Юр'єва, О.М.; Наконечна, Л.Т.; Пасік, Ю.С.; Курченко, І.М. (Фактори експериментальної еволюції організмів, 2014)
Aims. The aim of this research was to study the effect of the inductors of the cellulases and xylanase biosynthesis process. Methods. Cellulase activity has been measured by filter paper activity (exoglucanase) and viscosity reduction of Na-CMC solution (endoglucanase). Xylanase activity has been determined by hydrolysis of beech xylan. Results. Lactose, filter paper, arabinose, Na-CMC, wheat straw, sorbitol have been studied as possible inductors of cellulase and xylanase complex of Fennellia flavipes. The only wheat straw has induced significant value of cellulase and xylanase activity. Fennellia flavipes have not synthesized cellulase and xylanase, when it was cultivated on non-specific substrates. Conclusions. Effective synthesis of extracellular cellulase and xylanase complex by F. flavipes have been indicated that further research is a promising for obtaining of enzyme preparations and using for agricultural waste processing technology and cellulosic ethanol producing.